On the origins of sexual dimorphism in butterflies - Oliver, Jeffrey C. (The Royal Society, 2011)
The processes governing the evolution of sexual dimorphism provided a foundation for sexual selection theory. Two alternative processes, originally proposed by Darwin and Wallace, differ primarily in the timing of events creating the dimorphism. In the process advocated by Darwin, a novel ornament arises in a single sex, with no temporal separation in the origin and sex-limitation of the novel trait. By contrast, Wallace proposed a process where novel ornaments appear simultaneously in both sexes, but are then converted into sex-limited expression by natural selection acting against showy coloration in one sex. Here, we investigate these alternative modes of sexual dimorphism evolution in a phylogenetic framework and demonstrate that both processes contribute to dimorphic wing patterns in the butterfly genera Bicyclus and Junonia. In some lineages, eyespots and bands arise in a single sex, whereas in other lineages they appear in both sexes but are then lost in one of the sexes. In addition, lineages displaying sexual dimorphism were more likely to become sexually monomorphic than they were to remain dimorphic. This derived monomorphism was either owing to a loss of the ornament (‘drab monomorphism’) or owing to a gain of the same ornament by the opposite sex (‘mutual ornamentation’). Our results demonstrate the necessity of a plurality in theories explaining the evolution of sexual dimorphism within and across taxa. The origins and evolutionary fate of sexual dimorphism are probably influenced by underlying genetic architecture responsible for sex-limited expression and the degree of intralocus sexual conflict. Future comparative and developmental work on sexual dimorphism within and among taxa will provide a better understanding of the biases and constraints governing the evolution of animal sexual dimorphism.